CALCULATION OF THE AMPLITUDE AND POWER SPECTRUM OF INTERNAL WAVE IN THE SOUTH-EAST SEA REGION OF VIETNAM - Xuan, Nguyen Ba; Chung, Tran Van (Vietnam Journal of Marine Science and Technology, 2007)
In this paper some indirect calculations of the amplitude and power spectrum of internal wave are presented on basis of using the continuous temperature data measured at 2 moorings stations in the South-East sea region of Vietnam. The calculated results show that: In the shallow continental shelf region during the South-West monsoon, at the depths of 12 - 38 m, the average amplitude of internal wave has the values of 5 - 10 m; Whereas in the more deeper region during North-East monsoon, at the depths of 10 - 60 m, 70 - 220 m and 230 - 600 m, the average amplitude of internal wave has the values of 20 - 80 m, 1 - 5 m and 8 - 15 m respectively; By using the power spectrum analysis of internal wave show that: The power spectrum of internal wave in the shallow continental region is less than of about 20 times in comparison with the deeper region; The power spectrum of internal wave in the South-East sea region of Vietnam is complicated and formed mainly by waves having periods of 3 - 24 hours, among them, the wave components with periods of 12 and 24 hours are dominance. The waves with period smaller than 3 hours are very small power.